Fever with Thrombocytopenia in the Pediatric Age Group - Durfishan Dilshad, Ammara Jamal, Muniba Firoz, Mehak Gul, Mairah Raza, Ayesha Yasir, Sharmeen Nasir, Sania Saeed, (Pakistan Journal of Medical & Health Sciences, 2023)
Introduction: Fever with thrombocytopenia refers to a reduction in platelet count below 150,000/L in association with fever. Although febrile thrombocytopenia may occur due to aplastic anemia, malignancy or megaloblastic anemia, its commonest cause in the pediatric age group is infections like Dengue fever, Malaria and Enteric fever. Since infectious diseases are highly prevalent in our region we decided to determine the frequency of diseases associated with febrile thrombocytopenia in the pediatric age group. Objective: To determine the frequency of diseases associated with febrile thrombocytopenia in the pediatrics age group Study Design: Descriptive Cross-Sectional Study Place and Duration: Department of Paediatric Medicine, Civil Hospital, Karachi, Pakistan from November 22, 2018, to May 21, 2019 Methodology: After obtaining informed consent data related to signs, symptoms, clinical and confirmed diagnosis, and relevant lab results were recorded for children who fulfilled the inclusion criteria. Data were analyzed in terms of frequencies and percentages for qualitative variables like age group, gender and outcome variables. Results: Mean ± SD of age was 4.74±3.28. Out of 89 patients, 45(50.56%) were male and 44(49.44%) were female. In distribution for common causes of thrombocytopenia, 19 (21.3%) had malaria, 8 (9%) had dengue, 25 (28.1%) had an enteric fever, 32 (36%) had sepsis, 2 (2.2%) had malignancy and 3 (3.4%) had megaloblastic anemia. Conclusion: Sepsis, dengue, and malaria were the most frequent causes of thrombocytopenia. Therefore, anytime thrombocytopenia is found, more investigations can usually assist us in making the right diagnosis. Keywords: Febrile Thrombocytopenia, Malaria, Sepsis, Dengue, Enteric.